ISLAMIC SHARIA IN ACEH AND ITS IMPLICATIONS IN OTHER REGIONS IN INDONESIA - Yasrul Huda (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2020)
This article will discuss the impact of implementation of Sharia law in Aceh to other provinces in Indonesia, including West Sumatera. Considering the development of various regional regulations in West Sumatra, there are some things that need to be noted. First, the desire to make regional regulations consuisting sharia is more dominated by the desires of certain political parties. It is not supported by other government agencies in the form of existing local regulation follow-up even though the political party always claims that the regulation is the desire of the wider community. Consequently, it is difficult to reject the impression that the presence of these regulations is solely for the political interests of parties, or the interests of heads of government. Second, the emergence of these regulations is highly determined by the figures driving the emergence of these regulations. So, when they are no longer in their positions, then the attention to the implementation of these regulations is reduced or nonexistent. Third, there are differences of opinion or understanding among regional leaders that overcoming the problem of poverty, problems in education and the economy is far more important than just making sharia regulations. As a result of the accumulation of these three things, the momentum of the emergence of the need for sharia regulations often appears and then disappears and then reappears following certain events in the community; like in the month of Ramadan or other Islamic celebrations. Abstrak: Artikel ini akan membahas dampak penerapan syariat Islam di Aceh terhadap provinsi lain di Indonesia, termasuk Sumatera Barat. Melihat perkembangan berbagai peraturan daerah di Sumatera Barat, ada beberapa hal yang perlu diperhatikan. Pertama, keinginan untuk membuat peraturan daerah yang menganut syariah lebih didominasi oleh keinginan partai politik tertentu. Hal tersebut tidak didukung oleh instansi pemerintah lainnya berupa tindak lanjut perda yang ada, meskipun partai politik selalu mengklaim bahwa perda tersebut merupakan keinginan masyarakat luas. Akibatnya, sulit untuk menolak kesan bahwa kehadiran peraturan tersebut semata-mata untuk kepentingan politik partai, atau kepentingan kepala pemerintahan. Kedua, munculnya peraturan-peraturan tersebut sangat ditentukan oleh tokoh-tokoh pendorong munculnya peraturan-peraturan tersebut. Jadi, ketika mereka tidak lagi pada posisinya, maka perhatian terhadap pelaksanaan peraturan tersebut berkurang atau tidak ada. Ketiga, adanya perbedaan pendapat atau pemahaman di antara para pemimpin daerah bahwa mengatasi masalah kemiskinan, masalah pendidikan dan ekonomi jauh lebih penting daripada hanya membuat peraturan syariah. Akibat akumulasi dari ketiga hal tersebut, momentum munculnya kebutuhan akan peraturan syariah seringkali muncul, kemudian menghilang dan kemudian muncul kembali mengikuti peristiwa-peristiwa tertentu di masyarakat; seperti di bulan Ramadhan atau perayaan Islam lainnya. Kata Kunci: Hukum Syariah, Implikasi Syariah, Otonomi Khusus, Hukum Pidana Islam